Research on the choice of rational concentration of the gel forming agent in the composition of dental gel - Maslii, Yu; Ruban, O (Annals of Mechnikov’s Institute, 2019)
Taking into account the wide spreading and etiopathogenetic features of the course of inflammatory diseases of periodontium and oral mucosa, it is rational to use semisolid drugs of local action, namely, dental gels. The main issue when developing this dosage form is the choice of the gel former and its concentration. Based on previous studies as the gel basis for the development of a new dental gel with «Phytodent» tincture, choline salicylate 80%, and lidocaine hydrochloride the Carbomer Polacril® 40P, which is authorized for use in dentistry and has the ability to form transparent viscous aqueous-alcohol gels, has been chosen. It is known that rheological characteristics of gels directly affect the processes of release and absorption of active pharmaceutical ingredients from a semisolid dosage form, as well as its consumer properties. The important issue is the convenience and ease of application of a dental gel to inflamed tissues of periodontium and mucous membranes. This process is similar to that occurring during the shift of visco-plastic material in a rotary viscometer. The aim of the work is to study the structural and mechanical characteristics of the developed dental gel in order to select the rational concentration of the carbomer Polacril® 40P. Materials and methods. The study objects are gel samples with different concentrations of Carbomer Polacril® 40P – 1.0, 1.25, 1.5, 1.75 and 2.0 %. Measurement of the rheological parameters of the model gel samples was carried out at a temperature (25 ± 0.1) оС on a rotary viscometer with coaxial cylinders "Rheolab QC" ("Anton Paar") before and after contact with a solution of artificial saliva. As standards for comparison dental gels "Dentinox-gel N" (Germany) and gel "Metrogyl Denta®" (India) were selected. Results and discussion. It has been found that all gel samples have a non-Newtonian pseudoplastic flow type and are thixotropic systems with pronounced limits of fluidity. The rheological parameters of the dental gel samples increase as the concentration of Carbomer Polacril® 40P increases. In the nature of rheograms and structural viscosity the closest indicators to the drug "Dentinox-gel N" have gels with carbomer concentration of 1.25 % and 1.5 %, and to the drug "Metrogyl Denta®" – 1.75 % and 2.0 %. Conclusions. Taking into account the results of structural and mechanical studies of gels with and without an artificial saliva solution, as well as in terms of profitability, the optimal concentration of Carbomer Polacril® 40P in the composition of the developed gel was chosen to be 1.5 %.